Penerimaan Masyarakat Terhadap Sistem E-Voting dalam Pelaksanaan Pilkades di Desa Butuh Kecamatan Mojosongo Kabupaten Boyolali - Newa Idenanda; Rino Ardhian Nugroho; Teguh Budi Santoso (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
Electronic voting (e-voting) is the use of technology in general election, that can overcome the usually occur in conventional voting. This research aims to determine what factors influence public acceptance when using the e-voting system in the implementation of Pilkades in Butuh Village, Mojosongo Sub-Disctrict, Boyolali Regency by using Unified Model of Electronic Government Adoption (UMEGA). This study used quantitative methods and data collection using questionnaires. Sampling techniques using accidental sampling. The data analysis techniques used Partial Least Squares with the Smart.PLS 3.0 application. The result showed performance expectancy, effort expectancy, social influence, and attitude had a positive and significant effect on the behavioral intention of e-voting system users. While facilitating conditions and perceived risk are shown to have no effect on the behavioral intention of e-voting system users. And it was also found that the influence of user attitude successfully moderated the effect of performance expectancy, effort expectancy, and social influence on the behavioral intention of e-voting system users.